An Automatic System for Fishpond Ecology Monitoring and Control - razam, muhammad raimie; MOHID, ZAZULI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Expanding the industry and technology of controlled system requires developing the multifunctionality and performance of automatic system. Thus, a study on an automatic system for fishpond ecology monitoring and control for Ketutu fish had been conducted to identify the benefits to aquaculture field especially in fish productivity. Therefore, this project aimed to design, fabricate, and test a fishpond monitoring and control system. The scope of this study includes the development of system that focused on monitoring the water pH, and temperature. Moreover, this system is suitable for freshwater fish farmers who need to monitor their pond water quality. This monitoring and controlling system consist of Arduino Uno board, pH sensor, temperature sensor, dosing pump, relay module, shield data logger with DS1307 RTC, and LCD. Arduino Uno act as microcontroller to process signal from pH sensor and temperature sensor to get the real time monitoring value of pH and temperature of water to be display on LCD. The dosing pump function to supply buffer solution to water if the value of pH exceeds the range value between pH6.5 and pH7.5. Shield data logger with DS1307 RTC was use for easier collection of data. By realizing the control of aquaculture environment factors, and with helps of expert system, a real-time monitoring, data collection, read, store and comparison result had been successfully achieved. The study had revealed that if the value of pH exceeds the corresponding set points, it will automatically control to turn ON the dosing pump. The study also shows that when the system was ON, the water temperature slightly cooler compared to when the system is OFF. This automatic monitoring and control system is expected to be useful to monitor water quality for fishpond ecology.